On the Role of Culture in the Interaction Between Patient and Provider of Health Care - Vinck, Jan (ANIMA Indonesian Psychological Journal, 2008)
The process of the formation of illness representations is described, with special attention to the role of culture in this process. Illnes representations have strong effects on the emotional and coping reactions of the patient. Also via other ways, culture has an influence on the interaction of the patient with the providers of care, for example in terms of the risk of non-compliance with medical advice. In this paper the implications of these relations for practice are explored. Diuraikan proses pembentukan representasi penyakit, dengan perhatian khusus pada peran budaya dalam proses ini. Representasi penyakit memiliki pengaruh yang kuat terhadap reaksi emosional pasien dan cara mengatasinya. Juga lewat cara lain budaya memiliki pengaruh terhadap interaksi pasien dengan penyelenggara perawatan, misalnya dalam masalah risiko ketakpatuhan pada nasihat medis. Dalam artikel ini didalami implikasi hubungan tersebut dalam praktik.